2023
DOI: 10.3390/cells12192340
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effect of Variants in Toll-like Receptor 4 Gene in Saudi Patients with Type 2 Diabetes Mellitus

Zeina S. Alkudmani,
Amal F. Alshammary,
Imran Ali Khan

Abstract: Single-nucleotide polymorphisms (SNPs) in the Toll-like receptor 4 (TLR4) gene have been documented in type 2 diabetes mellitus (T2DM) and other diseases in the Saudi population. We investigated the relationship between rs11536889, rs4986790, and rs4986791 SNPs in the TLR4 gene and T2DM in the Saudi population; 105 patients with T2DM and 105 healthy controls were analyzed. The TLR4 gene was amplified through PCR, followed by restriction fragment length polymorphism analysis for rs4986791 and Sanger sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Both AG and GG genotypes were found to be causing a disease susceptibility locus for developing AML in the studied population. However, age and gender factors cannot be considered in this restricted case-control study as we have opted 100 AML cases and 100 controls based on the previous study towards the sample size enrollment ( Alkudmani et al, 2023 ). In control population of this study, the frequencies of AG and GG genotypes were found to be low when compared with AML cases.…”
Section: Discussionmentioning
confidence: 99%
“…Both AG and GG genotypes were found to be causing a disease susceptibility locus for developing AML in the studied population. However, age and gender factors cannot be considered in this restricted case-control study as we have opted 100 AML cases and 100 controls based on the previous study towards the sample size enrollment ( Alkudmani et al, 2023 ). In control population of this study, the frequencies of AG and GG genotypes were found to be low when compared with AML cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the relationship between GDF-15 gene polymorphism and human diseases [ 22 , 23 ], including gene polymorphism and the risk of DM [ 24 ]. The SNP analysis in this study showed that the risk of T2DM of rs1054564 GC and CC genotypes was higher than that of GG genotypes, which was consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of maintaining appropriate blood glucose levels for human health is often underestimated. The development of diabetes is typically linked to the disruption of the pancreas-insulin axis and the improper utilization of insulin [ 1 ]. T2DM is the most frequent kind concerning diabetes worldwide, affecting around 90% of individuals with diabetes.…”
Section: Introductionmentioning
confidence: 99%